PENGARUH KEPEMIMPINAN DAN PEMBERDAYAAN PEGAWAI TERHADAP KEPUASAN KERJA DAN KOMITMEN PEGAWAI (Studi Pada PDAM Tirta Mangutama Kabupaten Badung) - Putu Indah Afsari Devi (Jurnal Ekonomi dan Bisnis Jagaditha, 2017)
There is problem about Employee commitment of TirtaMangutama local water company (PDAM) in Badung Regency. The problem of commitment employee is related to several constructs such as : leadership, employee empowerment, and employee satisfaction. The aim of this study is understanding the influence of leadership and employee empowerment towards the employee satisfaction and employee commitment. The data is collected by questionnaire then will be treated by partial least square (PLS) in statistic method. There are 65 sample in this study and it collected by proportionate stratified random sampling method. The result of this study are : 1) leadership had negative effect and not significant with the employee commitment. 2) leadership had negative effect and not significant with employee satisfaction. 3) employee empowerment had positive effect and significant with employee satisfaction 4) employee empowerment had negative effect and not significant with employee commitment 5) employee satisfaction had positive effect and significant with employee commitment.